Potrebe, izzivi in dobre prakse pri jezikovnem poučevanju priseljencev - Pulko, Simona; Zemljak Jontes, Melita (Slavia Centralis, 2020)
THE NEEDS, CHALLENGES AND GOOD PRACTICES IN THE LANGUAGE TEACHING OF IMMIGRANTSEU societies and educational systems are becoming increasingly multicultural and multilingual due to the increased mobility and migration from EU and non-EU countries. Educational institutions are facing two challenges: to provide newcomer students with the possibility to acquire the language of education as soon as possible, and to help them to maintain their native language. This was the trigger to start the international Erasmus + DEAL Project Development of Literacy and Language Learning for Disadvantaged Young Learners (2018–2020) with institutions from Croatia, Northern Macedonia and Slovenia. The paper will present examples of good practice transferable to different languages.
Keywords: teaching methods; didactic approaches; Slovenian as a second and foreign language; Erasmus DEAL Project